Syphilis and HIV infection: an update - Zetola, Nicola M; Klausner, Jeffrey D (Clinical infectious diseases, 2007)
The striking increase in the prevalence of concordant human immunodeficiency virus (HIV) infection and syphilis observed by clinicians and public health officers over the past decade has renewed interest in the subject. Although the effect of HIV infection on the natural history of syphilis has been known for a long time, it was not until recently that several studies documented that syphilis may also impact the course of HIV infection. Despite an improved understanding of the interaction of these 2 conditions, many controversies still exist. In this article, we focus on the most recent literature describing the epidemiology, clinical manifestations, and treatment of syphilis in the context of HIV infection.